System of Nonlinear Set-Valued Variational Inclusions Involving a Finite Family of H(·,·)-Accretive Operators in Banach Spaces - Prapairat Junlouchai; Somyot Plubtieng (Journal of Applied Mathematics)
We study a new system of nonlinear set-valued variational inclusions involving a finite family of H(·,·)-accretive operators in Banach spaces. By using the resolvent operator technique associated with a finite family of H(·,·)-accretive operators, we prove the existence of the solution for the system of nonlinear set-valued variational inclusions. Moreover, we introduce a new iterative scheme and prove a strong convergence theorem for finding solutions for this system.